Proceedings of the 16th International Conference on Multimodal Interaction 2014
DOI: 10.1145/2663204.2663238
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Behavior Analysis in Depression Severity Assessment Interviews

Abstract: Previous literature suggests that depression impacts vocal timing of both participants and clinical interviewers but is mixed with respect to acoustic features. To investigate further, 57 middle-aged adults (men and women) with Major Depression Disorder and their clinical interviewers (all women) were studied. Participants were interviewed for depression severity on up to four occasions over a 21 week period using the Hamilton Rating Scale for Depression (HRSD), which is a criterion measure for depression seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
(66 reference statements)
1
29
0
Order By: Relevance
“…Consistent with alternative methods, and because we were interested in severity assessment and not in diagnostic, in preliminary work we investigated a number of possible vocal features for the measurement of depression severity. We considered both frequency and timing features such as fundamental frequency (f 0 ), Maxima Dispersion Quotient (MDQ), Peak Slope (PS), Normalized Amplitude Quotient (NAQ), Quasi Open Quotient (QOQ), and switching pause durations [11], [12]. However, preliminary results showed that only switching pause durations and f 0 were correlated with depression severity [11], [12].…”
Section: Audiovisual Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with alternative methods, and because we were interested in severity assessment and not in diagnostic, in preliminary work we investigated a number of possible vocal features for the measurement of depression severity. We considered both frequency and timing features such as fundamental frequency (f 0 ), Maxima Dispersion Quotient (MDQ), Peak Slope (PS), Normalized Amplitude Quotient (NAQ), Quasi Open Quotient (QOQ), and switching pause durations [11], [12]. However, preliminary results showed that only switching pause durations and f 0 were correlated with depression severity [11], [12].…”
Section: Audiovisual Feature Extractionmentioning
confidence: 99%
“…We considered both frequency and timing features such as fundamental frequency (f 0 ), Maxima Dispersion Quotient (MDQ), Peak Slope (PS), Normalized Amplitude Quotient (NAQ), Quasi Open Quotient (QOQ), and switching pause durations [11], [12]. However, preliminary results showed that only switching pause durations and f 0 were correlated with depression severity [11], [12]. For this reason, we used only these measures.…”
Section: Audiovisual Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent examples from the visual channel include smaller average distance between eyelids and shorter duration of blinks [6], slower head movements [7, 8], less head motion [710], longer duration of looking down [7, 11], decreased smiling [8, 11], decreased frowning, and increased mouth dimpling [8]. Recent examples from the acoustic channel include increased voice tension [11], decreased coordination among formant frequencies and cepstral channels [12], longer and more variable switching pauses [4], and decreased dyadic synchrony [13]. …”
Section: Identifying Behavioral Indicators Of Depressionmentioning
confidence: 99%
“…Studies exploring interpersonal measures are well-suited to exploring psychosocial theories; findings that depression is related to decreased dyadic synchrony [13] and longer and more variable switching pauses [4] suggest that depression interferes with interpersonal functioning in a measurable way. Of particular interest is an article by Girard et al [8], which tested the hypotheses of three clinical theories and, using automated analyses of facial expressions and head motion, found the strongest support for a novel psychosocial theory that nonverbal behavior serves to facilitate social withdrawal during periods of severe depression.…”
Section: Exploring Clinical Theories and Underlying Mechanismsmentioning
confidence: 99%